Comparative study of quantum mechanical Capacitance Voltage characteristics and threshold voltage of two different structures of Junction Less Nanowire Transistor - Tasneem, Nujhat; Adnan, Md. Mohsinur Rahman; Hafiz, Md. Samzid Bin (© 2016 IEEE, 2017)
This article presented at the IEEE Region 10 Annual International Conference [© 2016 IEEE] and the definite version is available at : https://10.1109/TENCON.2016.7848543. The article website is at: http://ieeexplore.ieee.org/document/7848543/